2019
DOI: 10.1186/s12943-019-1030-2
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between autophagy and epithelial-mesenchymal transition and its application in cancer therapy

Abstract: Autophagy is a highly conserved catabolic process that mediates degradation of pernicious or dysfunctional cellular components, such as invasive pathogens, senescent proteins, and organelles. It can promote or suppress tumor development, so it is a “double-edged sword” in tumors that depends on the cell and tissue types and the stages of tumor. The epithelial-mesenchymal transition (EMT) is a complex biological trans-differentiation process that allows epithelial cells to transiently obtain mesenchymal feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(207 citation statements)
references
References 149 publications
(152 reference statements)
8
198
1
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) refers to the epithelial cells transforming into mesenchymal cells, thereby gaining the process of interstitial cell phenotype [15]. EMT was reported to be involved in embryonic development, tissue remodeling, wound healing, tumor metastasis and other pathological physiological process [16].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) refers to the epithelial cells transforming into mesenchymal cells, thereby gaining the process of interstitial cell phenotype [15]. EMT was reported to be involved in embryonic development, tissue remodeling, wound healing, tumor metastasis and other pathological physiological process [16].…”
Section: Introductionmentioning
confidence: 99%
“…The link between EMT and autophagy has been amply demonstrated, since main pathways regulating autophagy have a dramatic impact on EMT, such as PI3K/AKT/mTOR, Beclin1, p53 and JAK/STAT signaling pathways. Additionally, signaling pathways implicated in EMT are crucial in autophagy, including integrins, WNTs, NF-kB, and TGF-β signaling pathways [123]. In CCA, EMT leads to immunosuppression through SNAIL expression [124] and is critical for invasiveness and metastasis induced by TGF-β1/SNAIL activation [125].…”
Section: Autophagy Modulation In Cholangiocarcinomamentioning
confidence: 99%
“…The signalling pathways of both EMT and autophagy are complex and can be induced in a number of ways; it is therefore unsurprising that there is some interaction between these two pathways [36,37] . Numerous studies in different contexts have demonstrated interactions between autophagy and EMT, although it does appear this is both context-and tissue-dependent [ Table 1].…”
Section: Emt and Autophagy: A Complex Relationship In Malignancymentioning
confidence: 99%